Does Tangible design and print hold value in the contemporary digital age? - Ellie Caitlin Hawker (Fields, 2021)
In the following study I have used a mix of trivial, journalistic and academic resources from relevant sources to draw a conclusion on the question posed; does tangible design and print hold value in the contemporary digital age? Explorations into the benefits of tangible design, how digital and material media is consumed, and the implications for design practice drove me to consider a range of elements to this query. These included reminiscence and nostalgia, the benefits of Lo-fi as an aesthetic choice, the freedoms that independent print media such as Zines can provide the designer and the unique sense of community that this can foster, how tangible design can be interactive in order to appeal to multiple senses and therefore create a deeper and more memorable connection for the consumer, and the unique set of benefits that come with stickers being such a tangible design media such as the appeal of free advertising and consumer freedoms of context choice. I also consider in this exploration the benefits of digital vs tangible when collaborating on a design piece. I drew the conclusion that tangible collaboration holds higher value due to more personal and time effective physical collaboration between multiple designers, however it must be said that digital collaboration brings forth its own set of benefits, such as allowing for long distance collaboration which may not otherwise be possible. When exploring how digital and tangible can be used not only for design but as tools to advertise design work and their comparable effectivity, I considered tangible design benefits such as stickers doubling as free advertising, and digital benefits such as being able to pay to reach larger audiences from broader scopes. The benefits considered by the stated explorations lead me to conclude that tangible print does still hold value in the contemporary digital age, which is proven by its still rife popularity.